The Effects of Institutional Quality and Human Capital Development on Economic Complexity in Africa: Empirical Evidence from Panel Data Analysis - Ojonta, Obed I. (Universitas Islam Indonesia, 2024)
The present study intends to investigate how the complexity of the economy responds to human capital investment and institutional development in Africa by employing the system GMM on panel data comprising 31 African economies over the period 2011-2020. However, earlier studies tended to ignore these interdependencies. More critically, our results indicate that the development of human capital enables the economic complexity in Africa. On the other hand, governance institutions’ quality in terms of control of corruption, voice and accountability, political stability, and the absence of violence and terrorism do not have any impact on economic complexity. Their effect on governance remains insignificant if governance is measured via government effectiveness, regulatory quality, and the rule of law. This research highlights the importance of diversifying African economies by promoting human capital investments and governance reforms that reduce corruption, ensure transparency and accountability in government, and stabilize politics. Our results also show that infrastructural development and GDP per capita are the major drivers of economic complexity in Africa, whereas international tourism appears to have a significant negative effect. Therefore, we provide several policy suggestions to reflect these insights.